2014
DOI: 10.1111/1567-1364.12136
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of genes involved in the oxidative stress tolerance using yeast heterozygous deletion collection

Abstract: In Saccharomyces cerevisiae, oxidative stress plays an inhibitory role during industrial fermentation. Although previous reports have identified genes required for oxidative stress tolerance, employing the yeast genome-wide screening, these screenings used a homozygous mutant collection which did not include the essential genes whose deletions result in lethality. Here, we report a truly genome-wide screening for the genes required for oxidative stress tolerance, using a heterozygous mutant collection which in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…Hence we used Fisher’s exact test to compare Rio1’s transcriptome dataset with those of other regulatory networks in yeast. We found that the Rio1 gene regulon significantly overlapped with those of the heat ( P -value = 1.4E-07), osmotic ( P -value = 3.7E-56), nutritional ( P -value = 7.2E-22) and oxidative ( P -value = 7.3E-04) stress-response systems (107–111) (the transcriptomes are size-weighted in Figure 7A, individual genes are listed in Supplementary Table S10). This observation suggested that Rio1 and its network are physically and functionally integrated with these response networks.…”
Section: Resultsmentioning
confidence: 91%
“…Hence we used Fisher’s exact test to compare Rio1’s transcriptome dataset with those of other regulatory networks in yeast. We found that the Rio1 gene regulon significantly overlapped with those of the heat ( P -value = 1.4E-07), osmotic ( P -value = 3.7E-56), nutritional ( P -value = 7.2E-22) and oxidative ( P -value = 7.3E-04) stress-response systems (107–111) (the transcriptomes are size-weighted in Figure 7A, individual genes are listed in Supplementary Table S10). This observation suggested that Rio1 and its network are physically and functionally integrated with these response networks.…”
Section: Resultsmentioning
confidence: 91%
“…Taurine is a solute required in osmoregulation, and has been linked to the survival of the fungus Ochroconis mirabilis in different habitats [69]. In the same functional category, we found candidate SNPs in genes such as a flavin-binding monooxygenase, and in the putative essential subunit of U3-containing 90S preribosome ( NOP9 ), which has been reported among the 71 essential genes required for oxidative stress tolerance in Saccharomyces cerevisiae [70]. Additionally we found the calcium channel subunit Cch1 , which has been reported to be involved in the Ca 2+ release in response to exogenous oxidative stress in yeast [71], and a putative flap endonuclease, which is part of the base-excision repair pathway that removes lesions resulting from exposure to reactive oxygen species in yeast [72, 73].…”
Section: Discussionmentioning
confidence: 99%
“…cerevisiae (S3B Table). The relevant variants were in DNA replication stress and DNA damage response ( RAS1 , RAS2 , RSR1 ) [26, 27] and cell wall integrity pathway ( PTS1 , ECM33 ) [28, 29], ER maintenance and oxidative stress ( SRP102 ) [30]. Some of these pathways were similar between MAC and RYT strains, suggesting these pathways are the primary response when fermentative ability of yeast is increased.…”
Section: Resultsmentioning
confidence: 99%